Investing in water management to improve productivity of rice-based farming systems in Cambodia - Johnston, Robyn M.; de Silva, Sanjiv; Try, Thuon (2014)
This study reviewed trends, issues and constraints affecting investments in agricultural water management in Cambodia. Informed by a review of current programs and the literature, workshops were convened in March 2013 to explore four keys areas: investments in irrigation, local institutions for managing irrigation, use of groundwater for irrigation and impacts of intensification on rice-field fisheries. We present some conclusions and unresolved questions here to promote a more broadly based debate around irrigation policy and investment in Cambodia. Drawing on the results of these workshops, policy briefs were compiled and published in English and Khmer.